Synthesis and biological activity of olomoucine II - Krystof, Vladimír; Lenobel, René; Havlícek, Libor; Kuzma, Marek; Strnad, Miroslav (Bioorganic & medicinal chemistry letters, 2002)
Based on our previous experiences with synthesis of purines, novel 2,6,9-trisubstituted purine derivatives were prepared and assayed for the ability to inhibit CDK1/cyclin B kinase. One of newly synthesized compounds designated as olomoucine II, 6-[(2-hydroxybenzyl)amino]-2-[[1-(hydroxymethyl)propyl]amino]-9-isopropylpurine, displays 10 times higher inhibitory activity than roscovitine, potent and specific CDK1 inhibitor. Olomoucine II in vitro cytotoxic activity exceeds purvalanol A, the most potent CDK inhibitor, as it kills the CEM cells with IC(50) value of 3.0 microM.
Keywords: Purines; viabilita buněk; proteinkinasa CDC28, S cerevisiae; protinádorové látky; CDC28 Protein Kinase, S cerevisiae; Structure-Activity Relationship; Drug Screening Assays, Antitumor; Kinetin; Roscovitine; Cell Survival; proteinkinasa CDC2; puriny; Enzyme Inhibitors; vztahy mezi strukturou a aktivitou; roskovitin; lidé; Humans; nádorové buňky kultivované; screeningové testy protinádorových léčiv; CDC2 Protein Kinase; Tumor Cells, Cultured; inhibitory enzymů; Antineoplastic Agents; kinetin